KEBIJAKAN PERANAN DINAS SOSIAL KABUPATEN LIMA PULUH KOTA DALAM PEMBINAAN ANAK JALANAN - Lira Mayanti; Wendra Yunaldi; Edi Haskar (Ensiklopedia of Journal, 2023)
Street children are one of the complex social issues that demand attention from the government and society. The Social Service has a crucial role in efforts to foster street children to help them overcome the challenges and difficulties faced and provide opportunities for a better life. policies and the role of the Social Service in fostering street children. This research uses the Empirical method to analyze data and information related to policies and programs that have been implemented by the Social Service in an effort to foster street children. The results of the analysis show that the Social Service has several important roles in fostering street children. First, the Social Affairs Office is responsible for collecting data and identifying street children in its area. This data collection aims to determine the number, characteristics, and problems faced by street children in order to design targeted programs. Second, the Social Services Office must organize a rehabilitation program for street children. This program includes care, education, skills training, and psychological support. The main goal of this rehabilitation program is to help street children overcome traumatization, develop their potential, and reintegrate back into society.